The manifesto : a guide to developing a creative career - Torrance, E. Paul (Ellis Paul), 1915-2003 (Publications in creativity research., 2002)
More than 40 years ago, E. Paul Torrance undertook to study creativity in students and study whether it would predict their creative achievements as adults. He and his colleagues wanted to determine what other factors influence, predict, encourage or sustain their creativity over time. There has never been a longitudinal study of creativity of this magnitude. The findings described here will be useful to, and have implications for, parents, teachers, counselors, instructors, and educational administrators.